Uncivilized Sexual Behavior Becomes Homosexual in Pendhalungan Adolescents in Jember Regency Using Miles Huberman's Analysis - Erdi Istiaji; Suryanto Suryanto; Andik Matulessy (Humanistic Network for Science and Technology (HNST), 2022)
Civilized behavior is a behavior that is acceptable to people in Indonesia, less civilized sexual behavior is a behavior that is deemed not in accordance with the behavior of the community, especially in shelter communities in the district of Jember. The phenomenon of psychological dynamism of sexual behavior that is considered Uncivilized in adolescents is interesting to study because homosexual behavior has not been accepted by shelter people who tend to still hold high religious values. This study focused to discribe psychologycal dinamycs in adolescent sexual behavior from those considered civilized to uncivilized from those who did not act homosexually to homosexuals. Researcher using a qualitative method with Miles Huberman analysis to describe, conclude and presenting data. This finding is different from other studies that find problems in the process of changing a teenager into homosexuality and is considered uncivilized by the community Keywords: uncivilized behavior; adolescent; homoseksual; Pendhalungan